Cadre As Early Education In Understanding Islam And Muhammadiyah - Mappanyompa Mappanyompa (International Consortium of Education and Culture Research Studies, 2020)
Collectively cadres are those who have been completed to follow all formal, tested in the informal cadre and have a provision through a non-formal cadre. Their existence is not only expected in the existence of the organization is maintained, but also expected the cadre will still bring the mission of organizational movement to the plenary. The Caderisasi occupies a very strategic position for the survival of Muhammadiyah as a requirement for the Islamic Da'wah and movement of the Islamist ma'ruf nahi munka. It is time for the caderisation to have a sincere attention from all the leadership of Muhammadiyah and the head of Muhammadiyah business charity, especially in West Nusa Tenggara whose condition is different from other regions, must be based on the intention Sincerely to live the Muhammadiyah and not merely seek life in Muhammadiyah as the founder's message the deceased KH. Ahmad Dahlan. Do not happen later that there are people who do not know the origins of the former will become the core player of Muhammadiyah or Muhammadiyah business charity, while people who are long-standing and unquestionably committed He was just the audience.